Transformative practices : the political work of public engagement practitioners - Escobar-Rodriguez, Oliver; Escobar, Oliver (The University of Edinburgh, 2014)
Participatory and deliberative democracy have attracted global attention, both as a field of research and practice. This interest reflects ongoing experimentation with ideas and practices of stakeholder governance, collaborative policy-making and citizen participation. The institutionalisation of such practices in Scotland is taking place through local partnership arrangements and public engagement processes. In particular, the Scottish Government’s Community Planning policy mandates local authorities to develop partnerships where various sectors and organisations are summoned to engage in collaborative policy-making. Central to this agenda is the involvement of citizens and communities through an increasing number of official local forums. In this sense, Scotland resembles other countries where public authorities seek working combinations of strategic partnership governance and local citizen participation. Despite burgeoning interest and developments, however, scarce attention has been paid to the role of public engagement officials tasked with turning participatory and deliberative ideals into everyday practices. Indeed, we still know little about the policy work of official ‘public engagers’ who organise participatory processes by negotiating a contested milieu of actors and agendas, while being constrained and enabled by an evolving ecology of participation. Consequently, this thesis presents findings from two years of ethnographic fieldwork shadowing public engagers in a Scottish Local Authority Area. The uniqueness of these policy workers is that their expertise is not on a particular policy area, but on stakeholder and citizen engagement across policy domains. That is, their expertise is on process, and their job is to facilitate deliberative forums to inform local policy-making. The fundamental question addressed here is not whether participatory policy-making works, but rather how does it work, what kind of work does it take, and what kind of work does it do. By foregrounding the ‘how’ question, this thesis provides a new practice-based analytical framework to both understand and inform participation processes. The findings highlight the importance of the engagers’ political work, thus illustrating the disciplinary force of engagement practice and the contested nature of participatory policy-making. Understanding these dimensions offers insight into new political spaces for the renegotiation of the relationship between authorities and citizens. Accordingly, the research shows how public engagers work to open and develop such spaces in order to foster new relationships through a new ‘politics of process’. In addition, it explores the impact that this work has on the engagers’ community of practice, as well as the challenges they face as engagement work gets institutionalised. Therefore, the thesis offers a distinct ethnographic account of the role of agency in developing official local spaces for participatory and deliberative democracy in Scotland.
Keywords: public engagement; participation practitioners; policy making